The role of nanobiotechnology in improving cryopreservation methods for cells and tissues - Dvinskykh, Anna; Khokhlenkova, Natalia; Kalyuzhna, Olha; Dvinskykh, Nataliia (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):250